Peran Fiksi Realistik Pada Novel Laskar Pelangi Dalam Mempertahankan Nilai BudayaPeran Fiksi Realistik Pada Novel Laskar Pelangi Dalam Mempertahankan Nilai Budaya - Cindy Berliana Latansyah; Dewi Sinta Febriani; Syarifah Aini; Takhta Adi Waskita; Yunita Widyastuti; Eni Nurhayati (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In the era of globalization and information technology, literature plays a crucial role in shaping cultural identity and enriching human knowledge and empathy. This journal discusses the role of realistic fiction in the novel "Laskar Pelangi" with a focus on the nature of human position, human relations with nature, and human relations. Through descriptive analysis, this research reveals the contribution of realistic fiction in maintaining cultural values. The findings show that novels are not only entertaining, but also present an in-depth look at everyday life and permeate cultural roots. Human position, relationship with nature, and social interaction are portrayed authentically, enriching readers' understanding of cultural values.